Devil’s claw has anti-neuroinflammatory capacity through mitochondrial recovering in microglia cells exposed to rotenone - Fagan Bissacotti, Bianca; Pappis, Lauren; Callegaro Velho, Maiara; Fontana, Tuyla; Kolinski Machado, Amanda; Geraldo Sangoi, Gabriela; Beroncal, Erika Leigh; Finger Schaffer, Larissa; Machado, Alencar Kolinski (Disciplinarum Scientia | Saúde, 2023)
Neuropsychiatric diseases, such as bipolar disorder, Alzheimer’s, and Parkinson’s disease, are related to mitochondrial dysfunction and chronic inflammatory activation, affecting thousands of people worldwide. Therefore, new alternative therapies with mitochondrial modulation and anti-inflammatory effects, especially involving natural agents are important to search. Harpagophytum procumbens is a notable candidate. It is an African plant with anti-inflammatory action. The objective of this study was to evaluate the anti-neuroinflammatory effect of H. procumbens ethyl acetate fraction in microglia cells. H. procumbens ethyl acetate fraction per se effect was available in SH-SY5Y and BV-2 cells during 24, 48, and 72 hours by cell viability and nitric oxide levels. Only BV-2 cells were exposed to rotenone to induce inflammation-mediated mitochondrial dysfunction and treated with curve concentration of H. procumbens fraction. Cellular proliferation and oxidative metabolism parameters were analyzed. Per se effect results revealed that significative changes are viewer depending on the time of exposure and cell line type. 0.001-400 µg/mL of H. procumbens treatment decreased nitric oxide and reactive oxygen species levels which have been increased by rotenone exposure, furthermore, cell viability recovered after this treatment exposure. H. procumbens was able to act as anti-neuroinflammatory agent, recovering mitochondrial complex I function, reducing oxidative stress, and decreasing cell proliferation.